2011
DOI: 10.20529/ijme.2011.012
|View full text |Cite
|
Sign up to set email alerts
|

Survey of “instructions to authors” of Indian medical journals for reporting of ethics and authorship criteria

Abstract: This study looked at information on ethics reporting and authorship in the "instructions to authors" section of Indian medical journals. Instructions to authors in 59 Indian medical journals were examined for guidance on ethics reporting and authorship. Guidance regarding ethics was mentioned in 43 (72.8%) journals; assent from minors was mentioned in 9 (15.2%) journals; approval from an animal ethics committee was mentioned in 10 (16.9%) journals; authorship criteria were mentioned in 38 (64.5%) journals. Aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…This percentage is much higher than the percentage reported by Salamat and coauthors 12 for Iranian medical journals (15%), slightly higher than the 59% reported by Wager for journals that belong to the World Association of Medical Editors, 8 but slightly lower than the 64.5% reported by Jaykaran and coauthors for Indian medical journals. 11 The study by Schriger and coauthors 10 did not establish the prevalence of authorship policies among a sample of journals but analysed the authorship policies among journals with a policy. While it is comforting to know that most scientific journals have an authorship policy, there is still room for improvement, especially among journals from the physical sciences/engineering or mathematical sciences and lower impact journals, which had a significantly lower percentage of authorship policies.…”
Section: Discussionmentioning
confidence: 99%
“…This percentage is much higher than the percentage reported by Salamat and coauthors 12 for Iranian medical journals (15%), slightly higher than the 59% reported by Wager for journals that belong to the World Association of Medical Editors, 8 but slightly lower than the 64.5% reported by Jaykaran and coauthors for Indian medical journals. 11 The study by Schriger and coauthors 10 did not establish the prevalence of authorship policies among a sample of journals but analysed the authorship policies among journals with a policy. While it is comforting to know that most scientific journals have an authorship policy, there is still room for improvement, especially among journals from the physical sciences/engineering or mathematical sciences and lower impact journals, which had a significantly lower percentage of authorship policies.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of health science journals have adopted the ICMJE recommendations in their policies [24,58]. The ICMJE recommendations help bring clarity, and provide useful reference points for the development and enhancement of authorship practices.…”
Section: Discussionmentioning
confidence: 99%
“…The adherence to the general and field-specific guidelines on authorship may be instrumental in curbing the conflicts globally and particularly in the emerging science countries, where a large proportion of journals still lack authorship policies and do not adhere to the accepted criteria (14). …”
mentioning
confidence: 99%